Studying cultural relevance in online courses: A thematic inquiry - Adams, Megan; Rodriguez, Sanjuana; Zimmer, Kate (Online Learning, 2019)
This study investigated if culturally relevant pedagogy was embedded into online reading courses at the undergraduate and graduate level in at a southeastern university college of education. The goals of the study were: to highlight the importance of a fully developed syllabus for adjunct and part-time faculty who rely heavily on the syllabus; to emphasize the importance of syllabi for curriculum and course integrity when programs move to fully online; to investigate whether the cultural relevance emphasized at the program level was evident in the syllabi. The findings indicate that alignment between assessment and objectives and a detailed syllabus in online courses are critical in creating culturally relevant online courses. This study is important to the field in several ways. First, colleges of education may benefit from the findings on explicit instructions in shared syllabi and in alignment in programs and courses. Additionally, including democratic classrooms and ensuring depth of knowledge in reading programs is important in program evaluation.